2017
DOI: 10.3892/etm.2017.5494
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑370 suppresses the progression and proliferation of human astrocytoma and glioblastoma by negatively regulating β‑catenin and causing activation of FOXO3a

Abstract: Abstract. Certain microRNAs (miRs) regulate the progression and metastasis of various cancer types. In the present study, the role of miR-370 in the progression and proliferation of human astrocytoma and glioblastoma cells was assessed and the underlying molecular mechanism was investigated. miR-370 levels in clinical specimens of human glioma and peritumoral tissues were determined by reverse-transcription quantitative PCR. Oligonucleotide mimics and inhibitors were transfected into the U-251MG human astrocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…Previous studies shows that miR-370-3p is down-regulated in human glioma cells [29] and its over-expression restrained GBM progression, including cell proliferation, migration and invasion, while promoting apoptosis [45]. MiR-370-3p inhibited the proliferation of human glioma cells by regulating the levels of β-catenin and the activation of FOXO3a [29,46]. A recent report showed that up-regulation of miR-370-3p sensitizes GBM cells to TMZ [28].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies shows that miR-370-3p is down-regulated in human glioma cells [29] and its over-expression restrained GBM progression, including cell proliferation, migration and invasion, while promoting apoptosis [45]. MiR-370-3p inhibited the proliferation of human glioma cells by regulating the levels of β-catenin and the activation of FOXO3a [29,46]. A recent report showed that up-regulation of miR-370-3p sensitizes GBM cells to TMZ [28].…”
Section: Discussionmentioning
confidence: 99%
“…Gliomas are classified into numerical grades (I–IV) according to the pathological classification of the World Health Organization (WHO) [ 2 ]. At present, despite undergoing aggressive surgical resection and a regular course of postoperative radiotherapy or chemotherapy, the overall 5-year survival rate for glioblastoma patients remains poor [ 3 , 4 ]. A number of crucial factors that contribute to the resistance of glioblastoma to standard therapeutic therapy have been reported, including genetic heterogeneity, multiple genetic lesions and dysregulated pathways [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, glioma is also 1 of the most malignant human brain tumors with high morbidity and low survival rates [2]. Clinical therapy of glioma depends on the size, type, grade, and location of the tumor, as well as the age and overall health of the patient, and mainly consists of surgical resection followed by radiotherapy, chemotherapy, Chinese medicine treatment, gene therapy, and so on [3]. However, the mortality or recurrence of glioma is still high because of resistance to traditional chemotherapy [4], and the in-depth pathogenesis of glioma remains to be elaborated, including aberrant activation of proto-oncogenes and inactivation of tumor suppressors [5].…”
Section: Introductionmentioning
confidence: 99%